Dynamics of globalization location-specific advantages or liabilities of foreignness? - Asmussen, Christian Geisler (Bingley, U.K. : Emerald, 2011)
Cross-border flows of goods, services, capital, knowledge, and ideas have substantially increased over the last decades. These developments have increased the interdependencies among previously separated economies, given rise to arguments regarding the flattening of the world. Yet, firms investing overseas continue to experience substantial liabilities stemming from their foreignness. At the same time new locations are appearing on the global map that offers very attractive location-specific advantages. In addition, the range of participants in international competition has widened, in terms of both the number of countries involved and the types of firms competing, to encompass developed market firms expanding beyond industrialized countries, and emerging market firms joining global competition. The focus of this volume is on how the interface between firm-specific advantages, liability of foreignness, and location-specific advantages are spelled out in the more global world.
Introduction to part I : Booz & Co./strategy + business eminent scholar in international management 2010 / Timothy M. Devinney -- The transnational transition and the multinational firm / Stephen J. Kobrin -- Connecting the plots : the contributions of Stephen J. Kobrin to international management research / Jonathan P. Doh -- Governance in a transnational era : Stephen J. Kobrin and the post-Westphalian reality / Ruth V. Aguilera -- Introduction to part II : dynamics of globalization : location-specific advantages or liabilities of foreignness? / Christian G. Asmussen, Torben Pedersen, Timothy M. Devinney, Laszlo Tihanyi -- The home-based advantages and a hierarchy of location resources : foreign and local firms dependency on location resources / Lilach Nachum -- The benefits of hierarchy? : exploring the effects of regional headquarters in multinational corporations / Phillip C. Nell, Bj$1'Xr(Bn Ambos, Bodo B. Schlegelmilch -- Overcoming liabilities of foreignness by modes of structural coordination : regional headquarters and their role in TNCs / Sven M. Laudien, J$1'Xr(Bg Freiling -- Moving abroad : factors that motivate foreign location of headquarter activities / Randi Lunnan, Gabriel R.G. Benito, Sverre Tomassen -- Selecting state or private joint venture partners in emerging markets : impact of liability of foreignness and rule of law / Indu Ramachandran, Kim Clark, Derrick McIver, Stewart R. Miller -- Liability of foreignness and location-specific advantages : time, space and relative advantage / Sjoerd Beugelsdijk -- Liability of foreignness and internationalisation of emerging market firms / Ajai S. Gaur, Vikas Kumar, Ravi Sarathy -- Evolution of firm- and country-specific advantages and disadvantages in the process of Chinese firm internationalization / Svetla Marinova, John Child, Marin Marinov -- From stages to phases : a theory of small developing country internationalization / Nigel L. Williams, Tom Ridgman, Yongjiang S. Shi -- What lies beneath the internationalization of firms in a regional innovation system? / Silvia R. Sedita, Fiorenza Belussi, Gianluca Fiscato -- Location determinants of FDI in sub-Saharan Africa : an empirical analysis / Satwinder Singh, Kirandeep Dhillon, Florian Kaulich, Weifeng Chen -- International entrepreneurship at the foreign market level : towards a network perspective / Sara Mel{u296E}, Emilia Rovira Nordman, Daniel Tolstoy, D. Deo Sharma -- The importance of internal and external knowledge sourcing and firm performance : a latent class estimation / Torben Pedersen, Christine Soo, Timothy M. Devinney -- A knowledge system approach to the multinational company : conceptual grounding and implications for research / Nicolai J. Foss, JosF.P. dos (Joe) Santos.s
Keywords: Globalization